Exploring Public Finance Policies: A Qualitative Inquiry into Fiscal Policy Analysis, Government Financial Management, and Public Sector Financial Health - Idrus, Arifin (Manunggal Halim Jaya, 2024)
This study explores the complexities of public finance governance, focusing on fiscal policy analysis, government financial management, and public sector financial health. Employing a qualitative research methodology, the study aims to analyze existing literature to uncover key themes, trends, and challenges in these domains. Through systematic literature review and thematic analysis, the research synthesizes insights from diverse disciplinary perspectives, including economics, public administration, and political science. Findings highlight the significance of fiscal policy as a countercyclical tool for promoting macroeconomic stability, the importance of effective financial management in ensuring transparency and accountability, and the multidimensional nature of public sector financial health. Challenges such as corruption, inadequate institutional capacity, and political interference are identified, underscoring the need for proactive measures to strengthen governance integrity. Innovative approaches, including accrual accounting standards and performance-based budgeting frameworks, offer promising solutions to enhance governance effectiveness and resilience. The study also emphasizes the role of adaptive governance strategies and agile financial management frameworks in responding to unforeseen crises while maintaining long-term fiscal sustainability. Future research directions include exploring the differential impacts of fiscal policy interventions, assessing the long-term implications of the COVID-19 pandemic, and examining the role of international cooperation in addressing global fiscal challenges.